Homomorphic Encryption for Big Data Security: A Survey - AL-Rummana, Galal A; Shende, GN (International Journal of Computer Sciences and Engineering, 2025)
The size of data generated every second has crossing the boundary of usual data size as a result of the rapid growth and spread of communication technology. This notable increase is of great importance and has gained the scholars’ interest. In other words, the increasing of data make the current ear an era of big data. Nowadays, one of the vital challenges is to get big data secured. Cryptography is an important technique that provides a high data security in many environments and applications. Homomorphic Encryption (HE), a special direction of cryptography, can address such security issues in big data environment. This paper concerns with the HE schemes which can play a vital role in securing big data environment. Therefore, big data concepts and characteristics are reviewed in the current paper along with full description of HE schemes, covering the HE types and illustrating their mechanisms for securing big data. In addition, the current paper offers some interpretations on the base of some security features along with big data security model.